2018
DOI: 10.1021/acs.joc.7b03125
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Catalyzed Dearomative Spirocyclization of N-Aryl Alkynamides for the Synthesis of Spirolactams

Abstract: A catalytic redox-neutral method for the synthesis of spirolactams proceeding through the dearomative spirocyclization of N-aryl alkynamides is reported. In contrast to stoichiometric activating agents employed for related transformations, we show that the use of 5 mol % of Au(PPh)Cl and AgOTf in dichloroethane at 50-80 °C leads to selective spirocyclization, furnishing the products in yields of 35-87%. The substrate scope of the reaction is good, with both electron-donating and electron-withdrawing groups bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…This general process was exemplified and exploited in the case of both alkynyl esters and amides (Scheme ). The group of Vadola described that both spirolactones 581 and lactams 583 could be obtained starting from the corresponding esters 580 or amides 582 (Scheme , part A). , Interestingly, while the dearomatization occurs in the presence of a methoxy group and water for the synthesis of lactones 581 , a tert -butyl ether or more simply a OH functionality is required in the case of lactams 583 . It was also shown that an Ugi MCR allowed for the rapid synthesis of diverse N -substituted lactams that could be readily cyclodearomatized under gold catalysis (see 584 ).…”
Section: Carbon π-Systems With Electron-withdrawing Groupsmentioning
confidence: 99%
“…This general process was exemplified and exploited in the case of both alkynyl esters and amides (Scheme ). The group of Vadola described that both spirolactones 581 and lactams 583 could be obtained starting from the corresponding esters 580 or amides 582 (Scheme , part A). , Interestingly, while the dearomatization occurs in the presence of a methoxy group and water for the synthesis of lactones 581 , a tert -butyl ether or more simply a OH functionality is required in the case of lactams 583 . It was also shown that an Ugi MCR allowed for the rapid synthesis of diverse N -substituted lactams that could be readily cyclodearomatized under gold catalysis (see 584 ).…”
Section: Carbon π-Systems With Electron-withdrawing Groupsmentioning
confidence: 99%
“…Synthesis of spirolactams via dearomative spirocyclization of Naryl alkynamides. [20] Scheme 4. Intramolecular dearomatization reaction of β-naphthol derivatives.…”
Section: Spirocyclization Via Dearomatization Reactionmentioning
confidence: 99%
“…Although the reaction is carried out in open air, the required temperature is 90 °C . A recent report by Vadola delineates a gold-catalyzed synthesis of spiroamides that proceeds through a dearomative alkyne insertion; however, the temperature required for the successful reaction was 80 °C, and Ag­(OTf) 2 was employed as an activator with moderate yields ranging from 35% to 80% …”
mentioning
confidence: 99%
“…From the experimental outcome mentioned above and the proposed mechanism of ruthenium-catalyzed oxidative dearomatization of indoles, a mechanistic outlook is proposed. The catalytic cycle begins with the oxidation of RuCl 3 ·3H 2 O to Ru­(VIII) in the presence of KBrO 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation